Degradation mechanism, intermediates and toxicology assessment of tris-(2-chloroisopropyl) phosphate using ultraviolet activated hydrogen peroxide. (February 2020) - Yu, Xiaolong; Yin, Hua; Peng, Hui; Lu, Guining; Liu, Zehua; Li, Huanyong; Dang, Zhi
Abstract: Organophosphate flame retardants (OPFRs), one kind of emerging flame retardants, have received prevalent attention owing to their ubiquity in aquatic matrices and their characteristics of being refractory to biodegradation. In current research, the degradation mechanism of tris-(2-chloroisopropyl) phosphate (TCPP), one of OPFRs, and its toxicological evaluation using UV-driven hydroxyl radical oxidation were investigated. A pseudo-first order reaction was fitted with an apparent rate constant ( K obs ) of 0.1328 min −1 on transformation of TCPP in the case of CH2 O2 0.1 mM, pH 6.6–7.1 and 4.7 mW cm −2 UV irradiation. High resolution mass spectroscopy analyses identified nine degradation products (eg., C6 H13 Cl2 O4 P ( m / z 251.0002), C9 H17 Cl2 O5 P ( m / z 307.0266), C9 H17 Cl2 O6 P ( m / z 323.0217), C9 H18 Cl3 O5 P ( m / z 343.0033)) during transformation of TCPP. The removal efficiency dropped by inhibitory effect of natural organic matters and anions, implying that the complete mineralization of TCPP may be difficult in actual water treatment process. The toxicity assessment has shown an decrease in reactive oxygen species (ROS) and apoptosis, membrane potential (MP) elevation of Escherichia coli, and biological molecular function revision (eg., metabolism and DNA biosynthesis), indicating that toxicity of degradation products were conspicuously decreased in comparison with intact TCPP. To sum up, effective detoxification of TCPP can be realized by a UV driving radical-based oxidation, which will provide an alternative safe treatment method to control TCPP in water matrix. Highlights: Rapid degradation of TCPP was induced by UV/H2 O2 oxidation. Hydroxy- and keto derivatives were identified by HRMS analyses. Toxicity evaluation of TCPP and its intermediates was conducted by flow cytometry. Incomplete degradation products exhibited less toxic than original TCPP. OH based-incomplete degradation conspicuously declined the TCPP toxicity.